10-Year Mortality Pattern Among Cancer Patients in Lagos State University Teaching Hospital, Ikeja, Lagos - Fatiregun, Omolara Aminat; Bakare, Omowunmi; Ayeni, Sunday; Oyerinde, Adebowale; Sowunmi, Anthonia C.; Popoola, Abiodun; Salako, Omolola; Alabi, Adewumi; Joseph, Adedayo (Frontiers in Oncology, 2020)
Background: Globally, cancer is a major leading health problem with an estimated 10 million incidences and 6 million cancer deaths annually. In Nigeria, an estimated 72,000 cancer deaths occur annually, and 102000 new cases are diagnosed from its population of 200 million people. These are, however, estimates, it is necessary to document the yearly trends and patterns of cancer mortality with regards to the different regions in the country. Methodology: We conducted this study at the Lagos State University Teaching hospital (LASUTH), Ikeja, Lagos to document mortality patterns from 2009 to 2018. Data extracted included those from the patient’s case notes, admission and death registers, and death certificates. we also had records from the hospital records department and medical wards. We then documented cancer mortality over the study period. Results: A total number of 6592 deaths were recorded over ten years, and 1133 cases were cancer-related deaths. This number puts the percentage of cancer-related deaths at 17.2%. Male patients accounted for 54.0%, and female patients are 46.0%. Breast cancer accounted for the highest mortality, followed by prostate cancer. The highest number of deaths were recorded in 2010 at 821, followed by 2011 at 799, 2015 at 780 and the least in 2017 at 513. There is also a significant general increase in odds of mortality with an increase in decades of life. Conclusion: This study shows that about one in five deaths, over the last ten years, from this tertiary institution, is related to a cancer diagnosis. Even though a yearly decline in the number of cancer deaths was noticed, probably due to increased awareness and governmental intervention, the percentage still remains high.